(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2015)
The Danish television series Forbrydelsen is representative of the successful intertwining of local narratives with transnational media within the scenario of contemporary Nordic Noir. This paper considers the series’ stylistic and production values to show how a “medium-concept” narrative, with its hybridization of genres, portrays highly debated social issues and raises a nationwide public discourse on them. The mingling of genres (melodrama and noir, sensational and crime fiction, and so on) produces a complex narrative that revolves around the wounded body and psyche of the female detective. The melodramatic mode of representation generates a dystopic vision of the contemporary world, visually depicting violent clashes between the individual and the agents of power, and the morally ambiguous compromises such clashes create for the nation.